Deleuzian 'interference' and emergent listening in intern teacher assemblages: singing in the (ref)rain. Issue 10 (25th November 2020) - Charteris, Jennifer; Nye, Adele; Jones, Marguerite
Abstract: The radical 'toolbox' of Deleuze and Guattari can equip us to investigate teacher education assemblages and teacher internship becomings. Three contributions of this paper comprise: a consideration of the refrain as an agile and underutilised education research concept; emergent listening, as an emerging theoretical framework in education; and transversality as a creative approach to research analysis. Accounts of teacher education refrain where there are both 'listening-as-usual' and 'emergent listening' are investigated. Emergent listening allows epistemological and ontological selves to be produced within research assemblages. Thus, Deleuzoguattarian geophilosophy can be used to unravel territorial positionings of what it is to be an 'acceptable' and/or 'successful' intern teacher within schooling socio-politics. Refrains, illustrated as research events, demonstrate territorialisations, deterritorialisations, and reterritorialisations in intern teachers' professional learning. The approach provides a way for teacher educators and researchers to recognise and map refrain movements and listening processes, in schooling, classroom and research assemblages.